A review of biofuel production from floating aquatic plants: an emerging source of bio‐renewable energy. (7th January 2021) - Arefin, Md Arman; Rashid, Fazlur; Islam, Amirul
Abstract: Aquatic plants have been considered as a cause for concern because they impede aquatic flora and fauna. However, biofuel production from aquatic plants is an emerging energy source. As a consequence, this paper presents a detailed review of bio‐fuel production from floating aquatic plants with their physicochemical properties. The main focus of this study is to evaluate the biofuel production potential of some major aquatic plants. This paper also presents some methods for biofuel production from aquatic plants that are feasible for future energy generation. Five major types of floating aquatic plants are analyzed in this study, viz. Azolla, water hyacinth, water fern, water lettuce, and duckweed, with their related biofuel production methodologies such as transesterification, pyrolysis, hydrolysis, and torrefaction. This paper also evaluates optimum bio‐fuel production conditions for aquatic plants and their upgradation methodologies. Conventional fuel and aquatic bio‐fuel properties are also compared in this study. Findings suggest that, depending on calorific value and viscosity, Azolla and water fern ( Salvania molesta ) are better aquatic plants to generate high‐quality (similar to diesel) biofuels compared with other aquatic plants. Bio‐fuel production from water fern, water lettuce, and duckweed are also comparatively less focused sources of energy. The cost associated with cleaning invasive aquatic plants from water can be turned into an investment by producing biofuel from aquatic plants using sustainable techniques. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd